The Relationship Between Family Support And Control Compliance In Mental Disordered Clients - Nurwijaya Fitri; Nova Mardiana; Ratu Hidyah Awaliyah (Citra Delima Scientific journal of Citra Internasional Institute, 2026)
Mental disorders are behaviors that are related to a person's mental health condition. Everyone person own see Which different aboutbehavior in the case Mental health is a person's emotional, psychological, and spiritual stability. The purpose of this study is to examine the relationship between family support and mental health. compliance control on client cross-section in 2025. This study used a cross-sectional design . with the independent variable (family support) and the dependent variable (control compliance). The population in this study was 118 people, and the sample size was 60 people, calculated using a simple random sampling method. This study was conducted on May 6, 2025. The results of the study using the Chi Square statistical test obtained the p-value of the variable support family 0.014 < 0.05. This indicates a significant relationship between family support and control compliance in clients with mental disorders at the mental health clinic at Depati Bahrin Sungailiat Regional Hospital in 2025. It is hoped that the suggestions in this study can be used as a reference source and provide a contribution of ideas for nursing students when carrying out practice in the field. so that students know factors Which Can affect compliance with control of clients with mental disorders.